2014
DOI: 10.1103/physreve.89.052803
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous point-process entropy: An instantaneous measure of complexity in discrete systems

Abstract: Measures of entropy have been widely used to characterize complexity, particularly in physiological dynamical systems modeled in discrete time. Current approaches associate these measures to finite single values within an observation window, thus not being able to characterize the system evolution at each moment in time. Here, we propose a new definition of approximate and sample entropy based on the inhomogeneous point-process theory. The discrete time series is modeled through probability density functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 32 publications
2
93
0
Order By: Relevance
“…Of note, this instantaneous assessment of complexity opens the possibility of analyzing the proposed measures also in terms of variability of their evolution along time -an idea which we refer to as our complexity variability framework [38]. Moreover, we have shown that the dynamical estimates and are not substantially affected by the type of noise underlying the complex system, thus ensuring truly instantaneous tracking of the complexity of the underlying dynamical system [38].…”
Section: Instantaneous Entropy Measuresmentioning
confidence: 95%
See 4 more Smart Citations
“…Of note, this instantaneous assessment of complexity opens the possibility of analyzing the proposed measures also in terms of variability of their evolution along time -an idea which we refer to as our complexity variability framework [38]. Moreover, we have shown that the dynamical estimates and are not substantially affected by the type of noise underlying the complex system, thus ensuring truly instantaneous tracking of the complexity of the underlying dynamical system [38].…”
Section: Instantaneous Entropy Measuresmentioning
confidence: 95%
“…Within this framework, Laguerre expansions of the Wiener-Volterra linear and nonlinear autoregressive terms account for long-term nonlinear information [36][37][38]. As major advantages, instantaneous measures can be estimated without applying any interpolation techniques to the RR interval series, and are associated to effective goodness-of-fit measures.…”
Section: Point-process Model Of the Heartbeatmentioning
confidence: 99%
See 3 more Smart Citations